Práticas territoriais de vigilância à saúde reprodutiva na estratégia saúde da família - Elias, Alessandra Nogueira (2013)
The research broaches territorial actions of reproductive health vigilance of Family Health Strategy (FHS), in Cuiabá, Mato Grosso. It analyzed the domiciliary and community actions of reproductive health vigilance effected and thought by workers that made them, recognizing the expressed perspective. The overarching health vigilance comprehends: the acknowledgement of the necessities of health in the territories and its consideration in the assistance practices; the integrated offer of individuals and collective actions of cure, prevention and promotion of health, in the humanized bases, valorizing especially the last; the formation of a bond among the families and services; and the articulation of a social network to health generation. To promote the reproductive health, besides reproducing these axes in the area, the actions of vigilance comprehend: the entailment of women, men and families in the reproductive health actions; the assistance approach of health to beyond the exclusive reproductive moment; and the politicization of reproduction to the appropriation of reproductive right and the equality in the reproductive matters, rescuing its interface with sexuality. It is a descriptive-exploratory study, qualitative, made in two units of Family Health in the city chosen, with 1 doctor, 2 nurses and 12 community health agents, through the participating observation and open interview. It was respected the demands of the ethics in research and it submitted the data to analysis of theme content. The territorial practice of reproductive health vigilance is made, above all, by community agents in domicile, through visits to pregnant women and puerperal, not existing specific action to men and families. The actions comprehend the investigation and/or information/orientation of women to problems of pregnant women/puerperal and about life behaviors and self care. They also involved inquiry, information/orientation and/or articulation to facilitation of access of woman to the local health service, to those of references, and, eventually, to social services. The technology used is connected to the control of medical problems, by the services or by the self care actions. The main aim of the actions is the control of risks and harm to pregnant women and puerperal. In the domicile visits there is a strong lack of planning, there is a belittling of the set of stages of assistance methodology and, in one of the territories, the lack of safety of the Community Health Agent doing of the 11 actions, besides the fact that the other workers being faraway. The production of data/information of reproductive health of the territory is made through visits and actions of registration of families, and registered in the file of Follow-up of the pregnant woman, in the Report of the Situation of Health and Follow-up of the Families of the Area, and eventually in the medical chart or retraced orally. This production is not used in the local planning and it does not implicate differentiated actions. The workers do not conceive the actions of oriented vigilance to prevention. The gestation and contraception are seen as theirs main object and the control as the most important mean. However, they accentuate the potential of the action approximating the workers to the local reality and in the articulation of several services actions. There is a restricted perspective of vigilance, expressed in the practice and in the workers conceptions. But in them there are potentialities to be develop. To promote changes, it is necessary to invest in the workers development, in the expansion of the purposes of the work process of the Family Helth and in the local/city conditions.